“Double whammy”: a rapid review of rural vs urban psychosocial cancer experiences and telehealth service in five countries during the COVID-19 pandemic - Marisa Barnes; Kylie Rice; Clara Murray; Einar Thorsteinsson (PeerJ, 2022)
Background Cancer is a long-term condition with biopsychosocial components. People with cancer living in rural areas can have poorer treatment outcomes and higher rates of unmet psychosocial needs than those in urban areas. Cancer, as opposed to other chronic conditions, poses a unique challenge in this current COVID-19 pandemic context, given immunocompromised states of patients and long-term survivor treatment effects. The disaggregated impact of psychosocial issues potentiated by the pandemic on rural vs. urban cancer populations is yet to be quantified. This rapid review investigates whether (i) people with cancer are experiencing pandemic-related psychosocial impacts, (ii) these impacts are equivalent in urban and rural locations, and (iii) whether the rapid uptake of telehealth mitigates or reinforces any identified impacts. Method A rapid review was conducted for literature published between December 2019 and 13 August 2021. Results Fifteen papers were included, incorporating evidence from five countries. The available literature suggests people affected by cancer living in rural areas are evidencing disproportionate psychosocial impacts of COVID-19, compounding cancer experiences. Despite its widespread and necessary use during the pandemic, telehealth was identified as an additional challenge for rural people with cancer. Conclusions Clinicians working with rural people affected by cancer should ensure recognition of the greater risks of psychosocial concerns in their rural patients, and reduced access to health services. Whilst telehealth and other remote technologies are useful and necessary in this pandemic era, clinicians should consider whether its use benefits their rural clients or reinforces existing disparities.